Avaliação da técnica APEX para o tratamento da síndrome da defecação obstruída associada à intussuscepção retal e prolapso mucoso circunferencial do reto - Regadas Filho, Francisco Sergio Pinheiro (2019)
Clinical evaluation of Apex technique for the treatment of the obstructed defecation syndrome associated with rectal intussusception and full rectal mucosal prolapse. Francisco Sergio Pnheiro Regadas Filho. Thesis (doctorate). Stricto Sensu Post-Graduation Program in Surgery. Advisor: Professor Dra. Sthela Maria Murad Regadas. Obstructed Defecation Syndrome is produced by functional (anismus) or anatomical alterations (rectocele, intussusception and rectal mucosal prolapsed). Several surgical techniques have been used in the treatment of such dysfunctions. The aim of this study was to evaluate anatomically and functionally patients undergoing surgical treatment using the APEX technique for the treatment of obstructed defecation associated with rectal intussusception and rectal mucosal prolapse. In an observation study, 40 patients (25 women and 15 men), mean age 58.4 years, with obstructed defecation symptoms due to rectal intussusception and/or rectal mucosal prolapse were evaluated. They were preoperatively evaluated through proctological examination, anal manometry and echodefecography. Patients with rectocele, enterocele and fecal incontinence were excluded. Two patients with anismus were initially treated with biofeedback. The parameters evaluated were Agachan-Wexner constipation score, the visual analogic pain scale (1-10) and postoperative anatomical evaluation through the ecodefecography. The mean constipation score significantly decreased from 14,4 to 4.8 in the postoperative period after a mean follow-up time of 119.2 days. Only 16 (40%) reported pain, 14 (35.0%) with mild pain according to the visual analogic scale (7 with a score of 1 and 7 with a score of 2). Two patients (5.0%) presented moderate pain with a score of 3. Ecodefecography demonstrated a complete reduction of rectal intussusception and a small residual mucosal prolapse was identified in 5 patients (12.5%) who were treated with application of rubber band ligation. In conclusion, the APEX technique is safe according with the low trans and post-operative complications and effective for the treatment of rectal intussusception and rectal mucosal prolapse, demonstrated by the significant reduction of the constipation score and the dynamic image exam, with. lower cost since only one circular mechanical stapler is used. Key words: Constipation. Obstructed defecation syndrome. Intussusception, Rectal mucosa prolapse. Mechanical stapler